PENGARUH MOTIVASI TERHADAP SKALA USAHA DAN PENDAPATAN PETERNAK SAPI POTONG DI EKS KARESIDENAN PATI - , Nur Aini Ika Fitri Fauzi; , Dr. Ir. Any Suryantini, MM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this study were to analyze the effect of motives (economics, social, and entertainment) as a substance of the motivation establishment of the farmers to the ownership of the business scale and income, and to recognize the number of cattle owned by farmers and income of the farmers simultaneously. Two districts sample was chosen by purposive sampling method, while 80 farmers were selected by purposive convenience sampling. The observed parameters were business scale, motives and income of the farmers. The income of the farmers was determined by calculating the differences between the total revenue and the total cost per animal unit per year. To understand the effect of the motives to the business scale and incomes was used the partial least square (PLS) model. The result of the study showed that the economics and social motives influenced significantly to the business scale and the income of the farmers, while the entertainment motive has no effect. The business scale have a significant effect on income. It was concluded that the most powerful motives that positively effect to the business scale and incomes of the farmers was the economic and social motives, while the entertainment motive has no effect to the business scale and incomes of the farmers. Motivation gave positive effect to the business scale and incomes of the cattle in Pati residency.